Evaluation of Khaya gum (Khaya senegalensis) as a polymer in the formulation of floating in situ gels of metoprolol succinate - Adenike Okunlola; Iyanu Abisoye Durodola (University of Huddersfield Press, 2023)
Metoprolol succinate, a β-selective adrenergic blocker, has a short half-life, low bioavailability, and high dosing frequency. In-situ gel drug delivery is a good approach to achieve sustained release for once-daily administration that will prolong drug retention time at the stomach and increase absorption. Thus, the aim of the study is to formulate floating in-situ gel formulations of metoprolol succinate using Khaya gum (Khayasenegalensis, family Meliaceae) as a polymer. Khaya gum was characterized and used in formulating in situ gels of metoprolol succinate in comparison with Hydroxyl Propyl Methyl Cellulose (HPMC K15M) and Xanthan gum. The in-situ gel formulations were characterized for appearance, swelling, in-vitro buoyancy and in-vitro drug release. FTIR revealed major peaks characteristic of the gum. Khaya gum showed high swelling and good flow properties. In-situ gel formulations of metoprolol succinate containing Khaya were light brown with near neutral pH, higher swelling and a total floating time >24 h, comparable to those containing HPMC and Xanthan gums. Dissolution time t80 was 60.50 to >240 min with ranking Khaya <HPMC <Xanthan. Khaya gum provides a cheaper, suitable polymer for formulating floating in-situ gels with prolonged buoyancy and drug release.